Numerical Analysis of the Transmission Model of Dengue on SEIR Model - Rattiya Sungchasit; Puntani Pongsumpun (My University, 2017)
In this paper, we used SEIR model to describe the transmission of dengue disease in mosquito due to the different dengue transmission rate in each season.Aedes aegypti and Aedes albopictus are primary vectors for the disease.The human population is separated into three population groups such as human in rainy season, human in winter season, human in summer season and vector population.We use standard dynamical analysis method for analyzing mathematical model.The basic reproductive number of disease is found.The stability conditions of the disease free equilibrium state for 1 0  R and the endemic state are determined for 1 0  R .
Keywords: Epidemic model; Mosquito-borne diseases and control